2010
DOI: 10.5012/bkcs.2010.31.5.1177
|View full text |Cite
|
Sign up to set email alerts
|

Gold Nanoparticles Coated with Gd-Chelate as a Potential CT/MRI Bimodal Contrast Agent

Abstract: The synthesis and characterization of gold nanoparticles coated by Gd-chelate (GdL@Au) is described, where L is a conjugate of DTPA (DTPA = diethylenetriamine-N,N,N',N'',N''-pentaacetic acid) and 4-aminothiophenol. These particles are obtained by the replacement of citrate from the gold nanoparticle surfaces with gadolinium chelate (GdL). The average size of GdL@Au is 12 nm with a loading of GdL reaching up to 1.4 × 10 3 per particles, and they demonstrate very high r1 relaxivity (~10 4 mM -1 s -1 ) and the r1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…One logical strategy was the combination of gadolinium chelates (Gd-DTPA or Gd-DO3A with high relaxation efficiency) with Au nanostructures (nanoparticles, nanorods, as well as nanoclusters with higher atomic number and strong X-ray attenuation property). [17][18][19][20] Moreover, Gd-DTPA modied lanthanide-based upconversion nanoparticles were also designed and prepared for MR and CT imaging. 21,22 The other strategy involved the doping of different lanthanide ions into a nanoplatform to achieve multi modal MRI/CT imaging probes.…”
Section: Instructionsmentioning
confidence: 99%
“…One logical strategy was the combination of gadolinium chelates (Gd-DTPA or Gd-DO3A with high relaxation efficiency) with Au nanostructures (nanoparticles, nanorods, as well as nanoclusters with higher atomic number and strong X-ray attenuation property). [17][18][19][20] Moreover, Gd-DTPA modied lanthanide-based upconversion nanoparticles were also designed and prepared for MR and CT imaging. 21,22 The other strategy involved the doping of different lanthanide ions into a nanoplatform to achieve multi modal MRI/CT imaging probes.…”
Section: Instructionsmentioning
confidence: 99%
“…Moreover, it is difficult to further functionalize the small molecules for targeting or other purposes (e.g., adding another imaging agent). , AuNPs have been demonstrated to be suitable as a contrast agent for CT imaging due to their high atomic number, superior absorption coefficient, and tunable particle size and morphology. A number of studies have reported the combination of Au nanospheres and Gd chelates for the preparation of multimodal MRI/CT contrast agents since the seminal work of Debouttière et al In addition, further studies, such as Gd-chelate-modified gold nanorods or nanospheres, Gd-enriched DNA AuNPs conjugates, and combining Gd chelates with gold nanostructures as multimodal MRI/CT contrast agents have been conducted. However, all of these reported Gd/Au-based multimodal contrast agents for MRI/CT imaging involve Gd chelate materials.…”
Section: Introductionmentioning
confidence: 99%
“…AuNPs are normally prepared using appropriate reducing agents, such as sodium borohydride, sodium thiocyanate, thiols, tannic acids, and ascorbic acids [44,45] . In most cases, stabilizing agents are used to prevent agglomeration and achieve a higher stability and growth.…”
Section: Resultsmentioning
confidence: 99%
“…AuNPs are normally prepared using appropriate reducing agents, such as sodium borohydride, sodium thiocyanate, thiols, tannic acids, and ascorbic acids. [44,45] In most cases, stabilizing agents are used to prevent agglomeration and achieve a higher stability and growth. However, biogenic surfaces with unique functionalities have grabbed the attention for the formation of AuNPs due to the associated green chemistry lending the process higher environmental credentials.…”
Section: Synthesismentioning
confidence: 99%